KARAKTERISASI MORFOLOGIS TEMBAKAU LOKAL KEBUMEN SEBAGAI UPAYA PELESTARIAN PLASMA NUTFAH - Barokah, Umi; Masyitoh, Siti; Arifin, Nurul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The tobacco plant is one of the plants cultivated in Kebumen Regency because it has high economic value compared to other plants. The varieties planted by farmers still use local varieties, namely Jero-Jlegi and Onthel. This variety has yet to be characterized, even though this tobacco plant is familiar to Kebumen farmers. The purpose of this study was to characterize morphologically and agronomically, namely, the production of local varieties of tobacco plants in Kebumen Regency, as an effort to preserve germplasm. The research was conducted in Peniron Village, Pejagoan District, Kebumen Regency. The results showed that the Jero-Jlegi variety tobacco plants had a plant height to the top leaf of 125cm, a plant height to a stem of 70 cm, a stem diameter of 2.5cm-3cm, a leaf length of 61cm, a leaf width of 36cm, a crown width of 109cm and a total of 10 leaves. The Onthel tobacco variety has a plant height to the top leaf of 131cm, a plant height to a stem of 66 cm, a stem diameter of 3cm, a leaf length of 67cm, a leaf width of 40cm, a crown width of 136cm and a total of 9 leaves. Ha) higher than the Onthel tobacco variety, 18.4 tons/day. Characterizing a plant will be very useful in selecting elders in a plant breeding program based on the variety's description. Keywords: tobacco, local, kebumen